Taxonomic detectives: unravelling the origins of Linnaeus’s Aspic viper (Vipera aspis) and assessment of the type material with designation of a neotype - Krecsák, László; Golay, Philippe; Åhlander, Erik; Cárdenas, Paco (Zootaxa, 2025)
We investigate the history and the fate of the specimen(s) that formed the basis of the description of one of the best-known venomous snakes, the Aspic viper, described as Coluber aspis by Linnaeus in 1758. Our study demonstrates that a thorough assessment of available historical literary sources and archived letters may recover the exact collection details for some Linnaean type-material. We show that Daniel Zachariae Hallman (1722-1782) collected the C. aspis type material in the surroundings of Bordeaux in 1754 or early spring 1755. Given that the holotype is missing from the collection of the Museum of Evolution at Uppsala University, we designate the male specimen MHNLR R.936 collected at Bois des Héros, commune of Port-d’Envaux (Charente-Maritime), southwestern France as the neotype for this species.